Ion solvated membrane and preparation method thereof

By blending and cross-linking the framework material and plasticizer, and adding hydrophilic inorganic particles, an ion solvated film with a pore structure connected to the large pores is formed, which solves the existing film's ion conductivity and electrolyte absorption capacity in the ionic conductivity and electrolyte absorption capacity. and mechanical strength deficiency, high-performance ion solvated film is achieved.

CN119400915APending Publication Date: 2025-02-07SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510936.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing ion solvated films have shortcomings in ion conductivity, electrolyte absorption capacity and mechanical strength, and it is difficult to meet the high-performance needs of electrochemical devices.

Method used

By blending and cross-linking the skeleton material and the plasticizer, and adding hydrophilic inorganic particles, an ionic solvated film with a pore structure in which small pores and large pores are formed.

Benefits of technology

It significantly improves the ion conductivity, electrolyte absorption and retention capacity and mechanical strength of the ionic solvated film, reduces production costs, and is suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400915A_ABST
    Figure CN119400915A_ABST
Patent Text Reader

Abstract

The invention discloses an ion solvated membrane and a preparation method thereof, the ion solvated membrane comprises a framework material and a plasticizer, and the ion solvated membrane comprises the framework material and the plasticizer, a pore structure formed between the framework material and the plasticizer comprises a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is communicated with the large pore structure. According to the ion solvation membrane provided by the invention, the porosity of the membrane is increased through the plasticizer, the pore structure and the ion migration channel of the membrane are improved, and the ion conductivity of the membrane is improved; meanwhile, the mechanical strength of the ion solvation membrane is improved, the hydrophilicity of the membrane is enhanced, permeation and absorption of electrolyte are promoted, the production cost is low, and large-scale commercial use is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical device diaphragms, and in particular to an ion solvation membrane and a preparation method thereof. Background Art

[0002] Ion solvation membranes refer to a special type of thin film material that can selectively conduct certain ions while blocking the passage of other ions. They have important applications in electrochemistry, energy storage and conversion devices (such as fuel cells and batteries).

[0003] The main materials of ion solvation membranes include perfluorosulfonic acid ion exchange membranes, polyimide membranes, polyphenylene ether membranes, polybenzimidazole membranes, lithium ion conductive membranes (such as ceramic electrolytes) and inorganic material membranes (such as alumina and zirconium oxide). The ion solvation membranes made of the above materials have the disadvantages of high cost and insufficient chemical stability. Polyvinyl alcohol is a good material for ion solvation membranes. It has high hydrophilicity and chemical stability and low cost. However, due to its semi-crystalline structure and the characteristics of molecular chain entanglement, polyvinyl alcohol membranes have the problems of low ion conductivity and poor electrolyte absorption capacity. In addition, polyvinyl alcohol membranes also have the problem of poor mechanical strength and are easy to break.

[0004] Therefore, how to provide an ion solvation membrane with high ionic conductivity, high electrolyte absorption capacity and high mechanical strength has become a technical problem that needs to be solved in the field of electrochemical device diaphragms. Summary of the invention

[0005] In view of this, the present application proposes an ion solvation membrane and a preparation method thereof.

[0006] According to the first aspect of the present application, an ion solvation membrane is proposed, which includes a skeleton material and a plasticizer, wherein the pore structure formed between the skeleton material and the plasticizer includes a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected to the large pore structure.

[0007] Specifically, the ratio of the average pore size of the small pore structure to the average pore size of the large pore structure is 1:3 to 1:1.1, preferably 1:2 to 1:1.5, and more preferably 1:2.5 to 1:1.8.

[0008] Specifically, the ion solvation membrane satisfies the following conditions:

[0009] The thickness of the ion solvation membrane is 120 μm to 300 μm; and / or

[0010] The alkali absorption rate of the ion solvation membrane is 156.5%-166.5%; and / or

[0011] The area swelling rate of the ion solvation membrane is no more than 20%; and / or

[0012] The volume swelling ratio of the ion solvation membrane is no more than 155%.

[0013] Specifically, the weight average molecular weight of the skeleton material is 89000-98000, and the molecular weight of the plasticizer is 950-1050.

[0014] Specifically, the skeleton material of the ion solvation membrane is one of polyvinyl alcohol and polyvinyl alcohol acrylic acid copolymer, preferably polyvinyl alcohol.

[0015] Specifically, the plasticizer is one of glycerol, propylene glycol, sorbitol, ethylene glycol, polyethylene glycol, citrates, phosphates, hexylene glycol, glycerol, pentaerythritol, xylitol, mannitol, sugar alcohol, biopolyol and isosorbide, preferably polyethylene glycol.

[0016] Specifically, the ion solvation membrane further includes hydrophilic inorganic particles, the diameter of the hydrophilic inorganic particles is 0.4 nm-4 nm, and / or the mass ratio of the hydrophilic inorganic particles to the skeleton material is 0.2:10-2:10.

[0017] Specifically, the hydrophilic inorganic particles are one of silicon dioxide, aluminum oxide, magnesium hydroxide, zirconium oxide, barium sulfate, titanium oxide and layered double metal hydroxide, preferably layered double metal hydroxide.

[0018] Specifically, the layered double metal hydroxide includes one of magnesium aluminum layered double metal hydroxide, zinc aluminum layered double metal hydroxide, nickel aluminum layered double metal hydroxide, cobalt aluminum layered double metal hydroxide, iron aluminum layered double metal hydroxide and nickel iron layered double metal hydroxide.

[0019] According to a second aspect of the present application, a method for preparing an ion solvation membrane is proposed, the preparation method comprising:

[0020] The skeleton material and the plasticizer are prepared into an ion solvation membrane so that a pore structure is formed between the skeleton material and the plasticizer, the pore structure includes a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected to the large pore structure.

[0021] Specifically, the preparation method comprises the following steps:

[0022] Mixing the skeleton material and the plasticizer to prepare a first solution;

[0023] preparing a second solution of hydrophilic inorganic particles;

[0024] The first solution and the second solution are mixed to form a third solution to prepare an ion solvation membrane.

[0025] Specifically, the third solution also includes a cross-linking agent solution, and the third solution is solidified through casting and cross-linking to form an ion solvation membrane.

[0026] Specifically, the crosslinking agent in the crosslinking agent solution is one of glutaraldehyde, borax, boric acid, diisocyanate, epoxy compound and chitosan, preferably glutaraldehyde.

[0027] Specifically, the weight percentage of the skeleton material in the first solution is 10.31%-10.47%, and the weight percentage of the plasticizer is 0.52%-1.04%.

[0028] Specifically, the mass volume ratio of the hydrophilic inorganic particles in the second solution is 0.02 g / ml-0.4 g / ml.

[0029] Specifically, the volume ratio of the first solution to the second solution is 7:2-17:1.

[0030] Specifically, the weight percentage of the cross-linking agent in the third solution is 0.1%-1%, preferably 0.3-0.7%.

[0031] The ion solvation membrane proposed in the present application has at least some of the following beneficial effects:

[0032] 1. The plasticizer increases the porosity of the membrane, improves the pore structure and ion migration channels of the membrane, and improves the ion conductivity of the membrane; increases the mechanical strength of the ion solvation membrane, enhances the hydrophilicity of the membrane, promotes the penetration and absorption of the electrolyte, and can also reduce production costs, which is conducive to large-scale commercial applications;

[0033] 2. The ion solvation membrane proposed in the present application has high ion conductivity, high electrolyte absorption and retention capacity, and high mechanical strength. The addition of hydrophilic inorganic particles improves the electrolyte absorption capacity of the composite membrane. Through the effective compounding and content adjustment of the plasticizer, a gourd-shaped microporous structure (small pores connected to large pores) can be formed inside the ion solvation membrane, which effectively promotes the absorption of electrolytes, thereby improving the electrolyte absorption and retention capacity and conductivity of the ion solvation membrane; by further adding a cross-linking agent to allow the skeleton material, plasticizer and hydrophilic inorganic particles to undergo in-situ cross-linking, the mechanical stability of the ion solvation membrane is improved;

[0034] 3. The preparation process of the ion solvation membrane provided by the present invention only includes stirring, paving and immersion steps, which is easy for large-scale production, and the raw materials are cheap and readily available;

[0035] 4. The ion solvation membrane provided by the present invention can be applied to alkaline water electrolysis and has excellent water electrolysis performance.

[0036] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings constituting a part of the present application are used to provide a further understanding of the present application, and the schematic implementation modes and descriptions of the present application are used to explain the present application. In the accompanying drawings:

[0038] Figure 1 These are microstructure diagrams of the nickel-iron layered double hydroxide of the present application and the ion solvation membrane prepared in Example 1, (a) is a microstructure diagram of the nickel-iron layered double hydroxide, (b) is a surface microstructure diagram of the ion solvation membrane prepared in Example 1, and (c) is a cross-sectional microstructure diagram of the ion solvation membrane prepared in Example 1.

[0039] Figure 2 This is a microstructure diagram of the ion solvation membrane prepared in Example 2 and Comparative Examples 1 and 3 of the present application.

[0040] Figure 3 This is a microscopic diagram of the outer surface of the ion solvation membrane prepared in Example 3 of the present application.

[0041] Figure 4 The area and volume inflation rates of the ion solvation membranes prepared in Comparative Examples 1-3, Examples 1-2, and Examples 4-5 of the present application.

[0042] Figure 5 The conductivity and alkali absorption rate of the ion solvation membranes prepared in Comparative Examples 1-3, Examples 1-2 and Examples 4-5 of the present application.

[0043] Figure 6 Polarization curves of the ion solvation membranes prepared in Comparative Example 1 and Examples 2-5 when used in an alkaline electrolytic cell. DETAILED DESCRIPTION

[0044] The technical solution of the present application will be described in detail below with reference to the accompanying drawings and in combination with the implementation modes.

[0045] Polyvinyl alcohol (PVA) is a high molecular polymer containing polyhydroxyl functional groups. Since the main chain does not contain arylene ether bonds and other polarized bonds, it has excellent stability in alkaline environments. Due to the polyhydroxyl structure of PVA, the formed membrane has good hydrophilic properties, and there is almost no obvious interface between the membrane and the electrolyte, which has the characteristics of ion solvation. Therefore, polyvinyl alcohol is one of the important raw materials for preparing ion solvation membranes. However, polyvinyl alcohol has limitations in terms of ionic conductivity, electrolyte absorption and retention capacity, and mechanical strength.

[0046] Therefore, in order to break through the limitations of traditional technology, the present application creatively utilizes the co-mixing and cross-linking of skeleton materials and plasticizers, and adds hydrophilic inorganic particles to synergistically improve the ionic conductivity of the ion solvation membrane. Co-mixing and cross-linking is to cross-link two different polymers of skeleton materials and plasticizers under the action of chemical bonds such as hydrogen bonds, thereby forming a stable cross-linked network. Polyvinyl alcohol is a polymer with tightly associated molecular chains. The introduction of plasticizers for cross-linking is conducive to enhancing the amorphous phase of polyvinyl alcohol and improving the kinetics of ion transmission. Adding hydrophilic inorganic particles in the ion solvation membrane is conducive to enhancing the hydrophilicity and electrolyte absorption capacity of the ion solvation membrane, thereby improving the ion transmission capacity of the ion solvation membrane.

[0047] The ion solvation membrane of the present application is based on a skeleton material as the basic skeleton, and then a plasticizer and a cross-linking agent are added for blending and cross-linking. The electrolyte absorption capacity of the ion solvation membrane is improved by adjusting the content of hydrophilic inorganic particles, reducing the hydrogen bonding effect between polyvinyl alcohol molecular chains to increase ion transmission channels, and enhancing the mechanical strength of the ion solvation membrane.

[0048] In the first aspect of the present application, an ion solvation membrane is proposed, which includes a skeleton material and a plasticizer. The pore structure formed between the skeleton material and the plasticizer includes a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected to the large pore structure.

[0049] The average pore size refers to the average pore size of large or small pores, which is calculated by dividing the sum of the diameters of large or small pores by the number of large or small pores.

[0050] The average pore size of the above-mentioned small pore structure and the average pore size of the large pore structure can both be measured under the microstructure.

[0051] The ion solvation membrane proposed in the present application has a pore structure in which small pores and large pores are connected. Through the synergistic effect of the skeleton material and the plasticizer, it provides high ionic conductivity, good mechanical properties and electrolyte retention ability; at the same time, the small pore structure contributes to good contact between the electrolyte and the electrode material, reducing the interface resistance; and improving the safety of use and cycle stability of the ion solvation membrane.

[0052] Specifically, the ratio of the average pore size of the small pore structure to the average pore size of the large pore structure is 1:3 to 1:1.1, preferably 1:2 to 1:1.5, and more preferably 1:2.5 to 1:1.8. It provides an efficient ion transmission channel, significantly improves ion conductivity, has a dense structure, can effectively prevent gas penetration, reduce gas cross contamination during the reaction, and improve reaction efficiency.

[0053] In order to ensure the performance of the ion solvation membrane, specifically, the ion solvation membrane can meet the following conditions: the thickness of the ion solvation membrane can be 120μm to 300μm; within this thickness range, the appropriate strength and ion conductivity of the ion solvation membrane can be provided to ensure the stability and effectiveness of the ion solvation membrane during use; and / or the alkali absorption rate of the ion solvation membrane can be 156.5%-166.5%; the ion absorption capacity of the ion solvation membrane with an alkali absorption rate within this range is relatively high, and it can effectively react with the electrolyte solution to improve the overall performance of the ion solvation membrane; and / or the area swelling rate of the ion solvation membrane is not greater than 20%; a lower area swelling rate indicates that the ion solvation membrane has better dimensional stability in a humid environment, which helps to maintain the structural integrity and function of the ion solvation membrane; and / or the volume swelling rate of the ion solvation membrane is not greater than 155%. Controlling the volume swelling rate within this range can ensure that the volume change of the ion solvation membrane after moisture absorption will not be too large, thereby maintaining the stability and performance of the ion solvation membrane during use.

[0054] In order to improve the mechanical strength and stability of the ion solvation membrane, specifically, the weight average molecular weight of the skeleton material can be 89000-98000, and the molecular weight of the plasticizer can be 950-1050. The skeleton material with a higher molecular weight gives the ion solvation membrane a higher mechanical strength and structural stability, so that the ion solvation membrane can resist mechanical stress and deformation; the plasticizer with a low molecular weight can penetrate between the molecular chains of the skeleton material, improve the flexibility and processability of the ion solvation membrane, maintain the strength of the ion solvation membrane, and the plasticizer can also improve the ionic conductivity of the ion solvation membrane, forming a flexible segment that is conducive to ion conduction, and optimizing the path to the point of the ion solvation membrane; the skeleton material with a high molecular weight improves the durability of the ion solvation membrane in the electrochemical environment, and the plasticizer with a low molecular weight ensures the stability of the ion solvation membrane during long-term use, and maintains good electrochemical properties.

[0055] In order to adapt to the complex electrochemical environment, specifically, the skeleton material of the ion solvation membrane can be one of polyvinyl alcohol and polyvinyl alcohol acrylic acid copolymer, preferably polyvinyl alcohol. As the skeleton material of the ion solvation membrane, polyvinyl alcohol has good mechanical strength, chemical stability and film-forming properties. Polyvinyl alcohol also has good water solubility and hygroscopicity, making it compatible with electrolyte solutions and easy to process into membranes of various shapes and thicknesses.

[0056] In order to improve the performance of ion solvation membrane, specifically, the plasticizer can be one of glycerol, propylene glycol, sorbitol, ethylene glycol, polyethylene glycol, citrates, phosphates, hexylene glycol, glycerol, pentaerythritol, xylitol, mannitol, sugar alcohol, biopolyol and isosorbide, preferably polyethylene glycol. Polyethylene glycol can effectively reduce the rigidity of ion solvation membrane, improve flexibility and processability, and has good chemical compatibility with skeleton materials, and can ensure the stability and uniformity of ion solvation membrane; through the effective compound and content regulation of polyethylene glycol, polyvinyl alcohol and polyethylene glycol can form (small holes connected to large holes) gourd-shaped microporous structure inside ion solvation membrane under the action of cross-linking agent, effectively promote the absorption of electrolyte, thereby improving the electrolyte absorption retention capacity and conductivity of ion solvation membrane. The water solubility and hygroscopicity of polyethylene glycol help to enhance the ionic conductivity of membrane, suitable for electrochemical applications.

[0057] In order to improve the ionic conductivity of the ion solvation membrane, specifically, the ion solvation membrane may also include hydrophilic inorganic particles, the diameter of the hydrophilic inorganic particles is 0.4nm-4nm, and / or the mass ratio of the hydrophilic inorganic particles to the skeleton material is 0.2:10-2:10. The hydrophilic inorganic particles increase the ionic conductivity and hydration capacity by introducing tiny pores or channels into the ion solvation membrane, and improve the stability and performance of the ion solvation membrane in a wet environment; at the same time, the pore structure of the ion solvation membrane can be optimized, and the mechanical strength of the ion solvation membrane can be improved. The physicochemical properties of the ion solvation membrane are adjusted, so that the ion solvation membrane has better performance in various electrochemical applications.

[0058] In order to improve the electrolyte absorption and retention capacity of the ion solvation membrane, specifically, the hydrophilic inorganic particles can be one of silicon dioxide, aluminum oxide, magnesium hydroxide, zirconium oxide, barium sulfate, titanium oxide and layered double metal hydroxides, preferably layered double metal hydroxides. Layered double metal hydroxides can significantly improve the electrolytic absorption capacity of ion solvation membranes. Layered double metal hydroxides are a type of metal hydroxide composed of two or more metal elements, and the structure is composed of the main layer plate and the anions and water molecules between the layers overlapping each other. There are a large number of hydroxyl groups between the layers, which are closely connected with water molecules through hydrogen bonding. The interlayer spacing provides space for the retention of water molecules, showing a high hydrophilicity. The layered structure of the layered double metal hydroxide provides a high ion exchange capacity, so that the ion solvation membrane can more effectively adsorb and release electrolyte ions, and enhance the ionic conductivity of the ion solvation membrane. In addition, the hydrophilic properties of the layered double metal hydroxide improve the hydration capacity of the ion solvation membrane, optimize the pore structure of the ion solvation membrane, and improve the penetration and distribution of the electrolyte. The chemical and structural stability of the layered double hydroxides also helps to maintain the electrolyte absorption and retention capacity of the ion-solvating membrane during long-term use.

[0059] In order to improve the mechanical strength and durability of the ion solvation membrane, specifically, the layered double metal hydroxide may include one of a magnesium aluminum layered double metal hydroxide, a zinc aluminum layered double metal hydroxide, a nickel aluminum layered double metal hydroxide, a cobalt aluminum layered double metal hydroxide, an iron aluminum layered double metal hydroxide and a nickel iron layered double metal hydroxide. Preferably, a nickel iron layered double metal hydroxide. The nickel iron layered double metal hydroxide not only exhibits excellent activity in electrocatalytic reactions and improves the electrolytic absorption capacity of the ion solvation membrane, but also has good ionic conductivity and excellent chemical stability, ensuring the stability of the ion solvation membrane in long-term use. The high hydrophilicity of the nickel iron layered double metal hydroxide enhances the hydration capacity of the ion solvation membrane, and its layered structure provides a stable three-dimensional network, which improves the mechanical strength and durability of the ion solvation membrane. In addition, the high specific surface area of ​​the nickel iron layered double metal hydroxide provides more active sites, further optimizing the electrolyte adsorption performance of the ion solvation membrane.

[0060] According to a second aspect of the present application, a method for preparing an ion solvation membrane is proposed, the preparation method comprising:

[0061] The skeleton material and the plasticizer are prepared into an ion solvation membrane so that a pore structure is formed between the skeleton material and the plasticizer, the pore structure includes a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected to the large pore structure.

[0062] Specifically, the preparation method comprises the following steps:

[0063] Mixing the skeleton material and the plasticizer to prepare a first solution;

[0064] preparing a second solution of hydrophilic inorganic particles;

[0065] The first solution and the second solution are mixed to form a third solution to prepare an ion solvation membrane.

[0066] When preparing the first solution and the second solution, an appropriate method may be selected, for example, they may be prepared simultaneously, or the first solution may be prepared first and then the second solution, or the second solution may be prepared first and then the third solution.

[0067] In order to improve the stability of the ion solvation membrane, specifically, the third solution may also include a crosslinker solution, and the third solution is cured by casting and crosslinking to form an ion solvation membrane. The volume concentration of the crosslinker in the crosslinker solution is 15%-25%, and the weight percentage of the crosslinker in the third solution is 0.1%-1%, preferably 0.3-0.7%. The use of a crosslinker enhances the mechanical strength and chemical stability of the ion solvation membrane, while ensuring the uniformity of the ion solvation membrane and the balance of physical properties, so that the ion solvation membrane performs well in a variety of applications.

[0068] In order to effectively improve the mechanical strength, chemical stability and overall performance of the ion solvation membrane, specifically, the crosslinking agent in the crosslinking agent solution can be one of glutaraldehyde, borax, boric acid, diisocyanate, epoxy compound and chitosan, preferably glutaraldehyde. Polyvinyl alcohol is a full carbon skeleton polymer with good alkali resistance and water solubility. Its linear structure limits its scope of application and performance. The crosslinking agent can play a bridging role between linear molecules, so that multiple linear molecules are bonded and crosslinked to form a network structure, thereby improving the physicochemical properties of the polymer. The aldehyde group in glutaraldehyde reacts with the hydroxyl group in polyvinyl alcohol to form a strong chemical crosslinking network, which improves the mechanical strength, structural stability and chemical tolerance of the ion solvation membrane, and improves the physical properties of the ion solvation membrane, such as thermal stability. The crosslinked ion solvation membrane has better ionic conductivity and stability.

[0069] In order to optimize the mechanical properties, ionic conductivity and stability of the ion solvation membrane, specifically, the weight percentage of the skeleton material in the first solution is 10.31%-10.47%, and the weight percentage of the plasticizer is 0.52%-1.04%. It is ensured that the ion solvation membrane has sufficient mechanical strength and structural stability, while maintaining high ionic conductivity and low swelling rate. The low plasticizer ratio helps to reduce volume changes and performance fluctuations, while optimizing material costs and processing performance, so that the ion solvation membrane is suitable for various electrochemical applications.

[0070] In order to ensure that the hydrophilic inorganic particles are evenly distributed in the ion solvation membrane, specifically, the mass volume ratio of the hydrophilic inorganic particles in the second solution can be 0.02g / ml-0.4g / ml. Within this concentration range, the agglomeration or deposition of the hydrophilic inorganic particles can be avoided, and the uniformity and consistency of the ion solvation membrane can be ensured; secondly, the appropriate concentration of hydrophilic inorganic particles can improve the ionic conductivity of the ion solvation membrane, and can also improve the physical properties of the ion solvation membrane, optimize the pore structure, enhance the mechanical strength and durability, and control the swelling behavior and volume change of the ion solvation membrane, thereby improving the overall performance of the ion solvation membrane.

[0071] In order to make the hydrophilic inorganic particles dispersed evenly in the solution and ensure the electrochemical performance of the ion solvation membrane, specifically, the volume ratio of the first solution to the second solution can be 7: 2-17: 1. It can ensure that the hydrophilic inorganic particles are evenly distributed in the ion solvation membrane, effectively balance the flexibility and mechanical strength of the ion solvation membrane, and avoid the increase in the brittleness of the ion solvation membrane caused by excessive hydrophilic inorganic particles. Secondly, an appropriate amount of hydrophilic inorganic particles can effectively improve the ionic conductivity and electrolyte absorption capacity of the ion solvation membrane.

[0072] The cross-linking agent solution used in the following Examples 1-5 and Comparative Examples 1-3 is a glutaraldehyde solution, and the concentration of the glutaraldehyde solution is 25%, that is, 25 g of glutaraldehyde is contained in 75 ml of water.

[0073] 1. Example of Ion Solvation Membrane Preparation Method

[0074] Example 1

[0075] A1. 10 g of polyvinyl alcohol and 0.5 g of polyethylene glycol were blended and dissolved in 85 ml of deionized water to form a first solution at 85 ° C;

[0076] A2. 0.5 g of nickel-iron layered double hydroxide (NiFe-LDH) was dissolved in 5 ml of deionized water and ultrasonically dispersed to form a second solution;

[0077] A3. The second solution is added to the first solution (the volume ratio of the first solution to the second solution is 7:2), mixed evenly, and 200 μl of glutaraldehyde solution (the weight percentage of glutaraldehyde is 0.6%) is added as a cross-linking agent to form a third solution; the amount of glutaraldehyde added is calculated as follows: (25÷75*0.2)÷(10+0.5+0.5+25÷75*0.2)*100%=0.067÷11.067=0.6%;

[0078] A4. 8 g of the third solution was naturally cast in a culture dish, and the solvent was induced to evaporate at room temperature. After it was naturally dried, an ion solvation film was obtained, and the ion solvation film was recorded as PPL-0.5.

[0079] Example 2

[0080] The method for preparing the ion solvation membrane of Example 1 is adopted, wherein:

[0081] A1. 10 g of polyvinyl alcohol and 1 g of polyethylene glycol were blended and dissolved in 85 ml of deionized water to form a first solution at 85 ° C;

[0082] A2. 0.5 g of nickel-iron layered double hydroxide (NiFe-LDH) was dissolved in 5 ml of deionized water and ultrasonically dispersed to form a second solution;

[0083] A3. The second solution is added to the first solution (the volume ratio of the first solution to the second solution is 12:1.5), mixed evenly, and 150 μl of glutaraldehyde solution (the weight percentage of glutaraldehyde is 0.43%) is added as a cross-linking agent to form a third solution; the amount of glutaraldehyde added is calculated as described in Example 1;

[0084] A4. Spread 8 g of the third solution evenly in a culture dish, induce the solvent to evaporate at room temperature, and after it is naturally dried, an ion solvation membrane is obtained, which is recorded as PPL-1.

[0085] Example 3

[0086] The method for preparing the ion solvation membrane of Example 1 is adopted, wherein:

[0087] A1. 10 g of polyvinyl alcohol and 2 g of polyethylene glycol were blended and dissolved in 85 ml of deionized water to form a first solution at 85 ° C;

[0088] A2. 0.5 g of nickel-iron layered double hydroxide was dissolved in 5 ml of deionized water and ultrasonically dispersed to form a second solution;

[0089] A3. The second solution is added to the first solution (the volume ratio of the first solution to the second solution is 17:1), mixed evenly, and 250 μl of glutaraldehyde solution (the weight percentage of glutaraldehyde is 0.66%) is added as a cross-linking agent to form a third solution; the amount of glutaraldehyde added is calculated as described in Example 1;

[0090] A4. Spread 15 g of the third solution evenly in a culture dish, induce the solvent to evaporate at room temperature, and after it is naturally dried, an ion solvation membrane is obtained, which is recorded as PPL-2.

[0091] Example 4

[0092] The preparation method of Example 2 is adopted, wherein:

[0093] A2. Dissolve 0.1 g of nickel-iron layered double hydroxide in 5 ml of deionized water and disperse by ultrasonic to form a second solution.

[0094] The prepared ion solvation membrane was designated as PPL1-0.1.

[0095] Example 5

[0096] The preparation method of Example 2 is adopted, wherein:

[0097] A2. Dissolve 2 g of nickel-iron layered double hydroxide in 5 ml of deionized water and disperse by ultrasonic to form a second solution.

[0098] The prepared ion solvation membranes were designated as PPL1-2.

[0099] Comparative Example 1

[0100] The method for preparing the ion solvation membrane of Example 2 is adopted, wherein:

[0101] A1. No polyethylene glycol is added to the first solution;

[0102] A2 is not included.

[0103] The prepared ion solvation membrane is denoted as PVA.

[0104] Comparative Example 2

[0105] The method for preparing the ion solvation membrane of Example 2 is adopted, wherein:

[0106] A2 is not included.

[0107] The prepared ionic solvation membrane was named PVAPEG.

[0108] Comparative Example 3

[0109] The method for preparing the ion solvation membrane of Example 2 is adopted, wherein:

[0110] A1. No polyethylene glycol is added to the first solution.

[0111] The prepared ion solvation membrane was named PVALDH.

[0112] The pore size test method of the ion solvation membrane of Examples 1-5 and Comparative Examples 1-3: Prepare 3 membrane samples for SEM cross-section testing. Under the condition of 5.0kV×1.00k, select an image range containing 5-10 large pores and 5-10 small pores, measure and record the pore size values, see Table 1.

[0113] Table 1 Pore size values ​​of ion solvation membranes

[0114]

[0115]

[0116] 2. Test methods

[0117] 2.1 Ultrastructural analysis

[0118] Scanning electron microscopy (SEM) was used to observe the ultrastructure of the outer surface and cross section of the nickel-iron layered double hydroxide and ion solvation membrane, respectively.

[0119] 2.2 Analysis of swelling behavior of ion-solvated membranes

[0120] Swelling behavior refers to the phenomenon that the volume or size of a membrane changes after absorbing a solvent (such as water or other liquid electrolytes). Swelling behavior is affected by many factors, including the material composition, pore structure, crosslinking density, and environmental conditions of the membrane. Moderate swelling can improve the ionic conductivity of the membrane because the absorption of the solvent facilitates the movement of ions in the membrane. However, excessive swelling can lead to a decrease in the mechanical strength of the membrane, structural instability, and even affect the overall function of the membrane. Therefore, controlling the excessive swelling behavior of ion-solvating membranes is the key to optimizing the performance of ion-solvating membranes.

[0121] The ion solvation membrane was cut into a 2 cm × 2 cm square. After measuring the thickness of the ion solvation membrane, the ion solvation membrane was immersed in a 6M KOH solution for 12 h. After the surface of the ion solvation membrane was taken out and naturally air-dried, the length, width and thickness of the ion solvation membrane were measured.

[0122] 2.3 Analysis of conductivity and alkali absorption rate of ion-solvated membrane

[0123] Conductivity is an important indicator to measure the ion migration ability in the membrane, which directly affects the performance of the membrane in electrochemical applications.

[0124] Alkali absorption rate refers to the ability of the membrane to absorb alkali in alkaline solution, usually expressed as the percentage of the mass of absorbed alkali relative to the dry weight of the membrane. Alkali absorption rate is an important indicator for evaluating the performance of membranes in alkaline environments, especially in electrochemical applications such as fuel cells, battery separators and other fields.

[0125] The ion solvation membrane was loaded into a PEEK conductivity cell, and the conductivity of the ion solvation membrane was measured by the electrochemical workstation (DH7003, Jiangsu Donghua Analytical Instrument Co., Ltd.) using the AC impedance method. At the same time, the alkali absorption rate of the ion solvation membrane was determined by the difference in mass of the ion solvation membrane before and after immersion.

[0126] 2.4 Alkaline water electrolysis test

[0127] The alkaline electrohydrolysis test is an important experiment for evaluating the electrochemical performance and stability of membranes in an alkaline environment. This test is often used to simulate actual application scenarios, such as alkaline fuel cells, electrolyzers, or other electrochemical devices that need to operate under alkaline conditions.

[0128] The alkaline water electrolysis test of the ion solvation membrane in this application is carried out in an alkaline electrolytic cell, which is mainly composed of a diaphragm, a double electrode, and an end plate. The ion solvation membrane is placed between the two electrodes to form a membrane electrode, which is then assembled with the end plate and a PTFE gasket for sealing into an electrolytic cell, and a circulating pump is connected to the cell to complete the circulation of the electrolyte.

[0129] 3. Test results

[0130] 3.1 Ultrastructure

[0131] Figure 1 (a) is the microstructure diagram of NiFe-LDH. It can be seen that NiFe-LDH has a layered structure. The layered structure of NiFe-LDH can provide specific channels for ion transport. Figure 1 (b) is the surface microstructure of the ion solvation membrane prepared in Example 1. It can be seen that the surface of the ion solvation membrane is relatively flat, indicating that NiFe-LDH, polyethylene glycol and polyvinyl alcohol have good compatibility, and the distribution of NiFe-LDH on polyvinyl alcohol is relatively uniform, which is conducive to the uniform absorption of electrolyte by the ion solvation membrane. Figure 1 (c) is a cross-sectional microstructure diagram of the ion solvation membrane prepared in Example 1. The interior of the ion solvation membrane presents an inconspicuous microporous structure. The presence of the pore structure in the membrane is conducive to the retention and transport of electrolytes in the membrane.

[0132] Figure 2 The microstructure of the ion solvation membrane prepared in Example 2, Comparative Example 1 and Comparative Example 3 is shown in FIG. Figure 2 It can be seen that compared with Comparative Example 1 (PVA) and Comparative Example 3 (PVALDH), the surface of the membrane of Example 2 (PPL-1) has some circular concave surfaces, which may be related to the change in the internal structure of the membrane. The cross-sectional scanning electron microscope showed that slit structures were observed in the membrane of Example 2 (PPL-1). The distribution of the slit structure in the membrane provides space for the absorption of the electrolyte and limits the evaporation of the electrolyte, thereby improving the OH - transmission.

[0133] Figure 3 The surface microstructure of the ion solvation membrane (PPL-2) prepared in Example 3 of the present application is Figure 3 a It can be seen that there are many larger pores on the surface of the ion solvation membrane. The larger pores provide good channels, allowing ions and small molecules to pass through the membrane faster, thereby improving the overall permeability of the membrane; Figure 3b is Figure 3 a A local enlarged view shows that the larger pores are not set independently, and multiple pores are interconnected. Multiple interconnected large pores can form an ion conductive network to improve the ion conductivity of the membrane; Figure 3 c is Figure 3 The local enlarged image of b shows that there are a large number of small pores distributed inside each large pore. The presence of small pores increases the specific surface area of ​​the membrane, promotes contact with the reactants, and thus enhances the reaction rate.

[0134] 3.2 Swelling behavior

[0135] like Figure 4 As shown, the area and volume swelling rates of Example 1 (PPL-0.5), Example 2 (PPL-1), Example 4 (PPL1-0.1) and Example 5 (PPL1-2) are greater than those of Comparative Example 1 (PVA), Comparative Example 2 (PVAPEG) and Comparative Example 3 (PVALDH), indicating that the ionic conductivity of the ion solvation membrane prepared in the examples is relatively better, and the swollen material can provide more channels, making ion migration more efficient and improving conductivity.

[0136] 3.3 Conductivity and alkali absorption rate

[0137] like Figure 5 As shown, the ion solvation membrane prepared in Example 2 (PPL-1) has the best alkali absorption rate of 161.5% and the conductivity of 51.63ms / cm 2 Much higher than Comparative Example 1 (PVA). This may be attributed to the synergistic effect of polyethylene glycol and NiFe-LDH: the 3D hydrogen bond network formed between polyvinyl alcohol, NiFe-LDH and polyethylene glycol provides a specific channel for ion transport. In addition, due to the microphase separation characteristics between high molecular weight polyethylene glycol and polyvinyl alcohol, the microporous structure formed inside the membrane provides space for the transmission and retention of electrolytes in the membrane. On the one hand, NiFe-LDH effectively enhances the amorphous region of polyvinyl alcohol, and on the other hand, the strong interaction between NiFe-LDH and polyvinyl alcohol effectively retains the electrolyte between the NiFe-LDH layers, thereby promoting the transmission of ions.

[0138] 3.4 Electrolytic performance

[0139] The thickness of the ion solvation membrane prepared in Comparative Example 1 (PVA) is 300 μm; the thickness of the ion solvation membrane prepared in Examples 2-5 is 300 μm, the anode is NiFe-LDH / NF, the cathode is Raney Ni, and the polarization curves of the electrolytic cells loaded with the ion solvation membranes prepared in Comparative Example 1 and Examples 2-5 are shown in FIG. Figure 6 When the single chamber voltage is 1.8V, the current density of Example 3 is 400mA / cm 2 When the single chamber voltage is 2V, the current density reaches 800mA / cm 2 Under the same voltage, the current density of Examples 2-5 is higher than that of Comparative Example 1, indicating that the electrolysis performance of the ion solvation membranes prepared in Examples 2-5 is better.

[0140] The ion solvation membrane proposed in the present application increases the porosity of the membrane through a plasticizer, improves the pore structure and ion migration channels of the membrane, and improves the ionic conductivity of the membrane; increases the mechanical strength of the ion solvation membrane, enhances the hydrophilicity of the membrane, promotes the penetration and absorption of the electrolyte, and can also reduce production costs, which is conducive to large-scale commercial applications.

[0141] The preferred embodiments of the present application are described in detail above; however, the present application is not limited to the specific details in the above embodiments. Within the technical concept of the present application, a variety of simple modifications can be made to the technical solution of the present application, and these simple modifications all fall within the protection scope of the present application.

[0142] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this application will not further describe various possible combinations.

[0143] In addition, the various implementation modes of the present application may be arbitrarily combined, and as long as they do not violate the concept of the present application, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An ion solvation membrane, characterized in that The ion solvation membrane comprises a skeleton material and a plasticizer, wherein the pore structure formed between the skeleton material and the plasticizer comprises a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected with the large pore structure.

2. The ion solvation membrane according to claim 1, characterized in that The ratio of the average pore size of the small pore structure to the average pore size of the large pore structure is 1:3 to 1:1.1, preferably 1:2 to 1:1.5, and more preferably 1:2.5 to 1:1.

8.

3. The ion solvation membrane according to claim 1, characterized in that The ion solvation membrane satisfies the following conditions: The thickness of the ion solvation membrane is 120 μm to 300 μm; and / or The alkali absorption rate of the ion solvation membrane is 156.5%-166.5%; and / or The area swelling rate of the ion solvation membrane is no more than 20%; and / or The volume swelling ratio of the ion solvation membrane is no more than 155%.

4. The ion solvation membrane according to claim 1, characterized in that The weight average molecular weight of the skeleton material is 89000-98000, and the molecular weight of the plasticizer is 950-1050.

5. The ion solvation membrane according to claim 4, characterized in that The skeleton material of the ion solvation membrane is one of polyvinyl alcohol and polyvinyl alcohol acrylic acid copolymer, preferably polyvinyl alcohol.

6. The ion solvation membrane according to claim 4, characterized in that The plasticizer is one of glycerol, propylene glycol, sorbitol, ethylene glycol, polyethylene glycol, citrate esters, phosphate esters, hexylene glycol, glycerol, pentaerythritol, xylitol, mannitol, sugar alcohol, biopolyol and isosorbide, preferably polyethylene glycol.

7. The ion solvation membrane according to claim 1, characterized in that The ion solvation membrane further comprises hydrophilic inorganic particles, the diameter of the hydrophilic inorganic particles is 0.4 nm-4 nm, and / or the mass ratio of the hydrophilic inorganic particles to the skeleton material is 0.2:10-2:

10.

8. The ion solvation membrane according to claim 7, characterized in that The hydrophilic inorganic particles are one of silicon dioxide, aluminum oxide, magnesium hydroxide, zirconium oxide, barium sulfate, titanium oxide and layered double metal hydroxides, preferably layered double metal hydroxides.

9. The ion solvation membrane according to claim 8, characterized in that The layered double metal hydroxide includes one of magnesium aluminum layered double metal hydroxide, zinc aluminum layered double metal hydroxide, nickel aluminum layered double metal hydroxide, cobalt aluminum layered double metal hydroxide, iron aluminum layered double metal hydroxide and nickel iron layered double metal hydroxide.

10. A method for preparing an ion solvation membrane, characterized in that: The preparation method comprises: The skeleton material and the plasticizer are prepared into an ion solvation membrane so that a pore structure is formed between the skeleton material and the plasticizer, the pore structure includes a small pore structure with a relatively small average pore size and a large pore structure with a relatively large average pore size, and the small pore structure is connected to the large pore structure.

11. The preparation method according to claim 10, characterized in that: The preparation method comprises the following steps: Mixing the skeleton material and the plasticizer to prepare a first solution; preparing a second solution of hydrophilic inorganic particles; The first solution and the second solution are mixed to form a third solution to prepare an ion solvation membrane.

12. The preparation method according to claim 11, characterized in that: The third solution also includes a crosslinking agent solution, and the third solution is cured through casting and crosslinking to form an ion solvation membrane.

13. The preparation method according to claim 12, characterized in that: The crosslinking agent in the crosslinking agent solution is one of glutaraldehyde, borax, boric acid, diisocyanate, epoxy compound and chitosan, preferably glutaraldehyde.

14. The preparation method according to claim 11, characterized in that: The weight percentage of the skeleton material in the first solution is 10.31%-10.47%, and the weight percentage of the plasticizer is 0.52%-1.04%.

15. The preparation method according to claim 11, characterized in that: The mass volume ratio of the hydrophilic inorganic particles in the second solution is 0.02 g / ml-0.4 g / ml.

16. The preparation method according to claim 11, characterized in that: The volume ratio of the first solution to the second solution is 7:2-17:

1.

17. The preparation method according to claim 12, characterized in that: The weight percentage of the cross-linking agent in the third solution is 0.1%-1%, preferably 0.3-0.7%.